PDMS-based porous particles as support beds for cell immobilization: Bacterial biofilm formation as a function of porosity and polymer composition - Fernandez, Marcelo Raul (2010)
The objective of this work is to test the performance of new synthetic polydimethylsiloxane (PDMS)-based bed particles acting as carriers for bacteria biofilms. The particles obtained have a highly interconnected porous structure which offers a large surface adsorption area to the bacteria. In addition, PDMS materials can be cross-linked by copolymerization with other polymers. In the present work we have chosen two hydrophilic polymers: xanthan gum polysaccharide and tetraethoxysilane (TEOS). This versatile composition helps to modulate the interfacial hydrophobic/hydrophilic balance at the particle surface level and the roughness topology and pore size distribution, as revealed by scanning electron microscopy. Biofilm formation of a consortium isolated from a tannery effluent enriched in Sulphate Reducing Bacteria (SRB), and pure Acidithiobacillus ferrooxidans (AF) strains were assayed in three different bed particles synthesized with pure PDMS, PDMS-xanthan gum and PDMS-TEOS hybrids. Bacterial viability assays using confocal laser scanning fluorescence microscopy indicate that inclusion of hydrophilic groups on particle's surface significantly improves both cell adhesion and viability. © 2010 Elsevier B.V.